Subway station seismic consideration based on geotechnical study: a case study approach - Ghiasi, Vahed; Omar, Husaini; Kazemian, Sina; Ghiasi, Samad; Kim Huat, Bujang; Muniandy, Ratnasamy; Baharvand, Moharam; Hosaini, Seyed Ghavamoddin; Souri, Morteza; Prasad, Arun; Md Yusoff, Zainuddin; Safaei, Mehrdad (Academic Journals, 2011)
Iran is a vast country with 1.6 million square kilometer area and more than 70 million inhabitants. Tehran, the capital of Iran, together with its satellite townships is home to more than one sixth of the country's population which make over 13 million, and mostly make motorized daily journeys. This work is based on the case study geotechnical investigation of a metro station in Tehran. The access gallery and tunnel inter-section problem is very sensitive and dangerous in critical zones and the necessity of the provision of tunnel lining has been discussed in this paper. This study is a concise case study which highlights the important soil parameters for designing of deep and shallow tunnels and substations. It shows the critical area for performance of tunnel intersection of and access galleries and the method to avoid collapse of the tunnel and access galleries while tunneling with a high safety. If boring of the access gallery and tunnel station, is made at the same time or the boring of the access gallery is carried out before the tunneling lining, the tunnel will be overburdened with loads leading to weakening of the access galleries crown, and its immediate collapse. One of the objectives of this paper is defining the seismic modeling of tunnel. Specifying the differences in seismic modeling using two softwares, PLAXIS and FLAC is another aim of this paper.